A study on the impact of the Panama canal expansion on major stakeholders - Yong, Lee Ping (2015)
To cope with the increasing trend towards bigger vessels and stay competitive in this era, the expansion of the Panama Canal, which is reaching its maximum capacity, is deemed necessary to accommodate the enlarged dimensions of the vessels and higher traffic. Scheduled for completion in 2016, the canal expansion is projected to have global impacts on commercial shipping and port operations, with a likely consequence of shifting trade patterns. Our project aims to discuss and analyse the potential impacts of Panama Canal expansion from the different viewpoints of the major stakeholders, consisting of Panama, port users, terminal operators as well as the environment. As Singapore may be affected in consideration of the change in shipping patterns, this research project investigates the different perspectives of the main players in the local shipping industry, including container shipping, oil and gas shipping, dry bulk shipping and terminal operator. This research report focuses on one of the three work packages: The Port Users. It is important for shippers and carriers to justify the costs and benefits for deploying larger vessels to transit the Panama Canal as compared to the Suez Canal or other available trade routes. The potential cost savings by transiting via the canal may enhance the attractiveness of the Panama Canal within the next 10 to 20 years, accelerating the shift of shipping trade routes. Not only the new cargo potentials such as dry bulk and Liquefied Natural Gas (LNG) are evaluated, but the opportunities and threats for port users are also assessed. On top of the secondary research done, survey and interviews were conducted to gather industry opinions and analyse the key findings in order to gain an overall understanding of the work package relevant to the study.